Trocas gasosas e características produtivas de plantas de soja em condições de encharcamento do solo e restrição luminosa - Cecatto Júnior, Roberto (2020)
The root tissues of soybean plants in soaked soil, with low oxygen content, have reduced aerobic respiration activity, causing metabolic disorders that negatively affect gas exchange and photosynthetic activity, impairing growth and production. The growth and production of soybeans are also negatively affected by the decline in the incidence of solar radiation, as it affects gas exchange and the functioning of the photosynthetic apparatus. Thus, the objective of the study was to investigate the effects on gas exchange, photosynthetic activity curves as a function of light, growth and production of soybean plants subjected to soaked soil and light restriction conditions. This study aimed to evaluate the treatments: plants in a stress-free condition, plants with light restriction, plants in soaked soil, and plants in soaked soil + light restriction. To impose the light restriction, a shading screen with the capacity to retain 80% of the incident light was used. Soil drenching was carried out keeping the soil above field capacity. The imposition of treatments occurred simultaneously, starting at full flowering (R2), extending for 30 days until grain filling (R5.2). At 15 days of stress imposition, it was determined: gas exchange every two hours throughout the day, relative chlorophyll content, specific leaf area and liquid photosynthesis depending on the light. Twenty days after the imposition of treatments were also determined: leaf gas exchange and relative chlorophyll content. After 30 days of treatment imposition, it was determined: morphometry and nutrient content in the leaves. At the end of the crop cycle, the production and production components per plant were determined. Soybean plants subjected to development in soaked soil and environment with light restriction alone or together throughout the day showed a decline in liquid photosynthesis, reduced stomatal opening and transpiration. Plants exposed to light restriction for a period of 15 days, showed acclimatization that allowed greater apparent quantum efficiency and increased photosynthesis in an environment under low light incidence. Plants subjected to development for 15 days in soaked soil, in full sun, presented chlorotic leaves and reduced apparent quantum efficiency and consequently presented a decline in photosynthesis under low light or high light. Exposure to soil flooding conditions and light restriction for a period of 20 days caused a decline in net photosynthetic rates, transpiration and stomatal conductance. In addition, exposure to the condition of soaked soil caused the development of leaves with a chlorotic aspect and reduced levels of leaf nutrients and less accumulation of dry mass. Exposure to light restriction, in soaked soil or normal irrigation, reduced the accumulation of dry matter and caused plant etiolation. Soybean plants in the conditions of soaked soil and light restriction alone or together, between the beginning of full flowering (R2) until the filling of grains (R5.2), provided a reduction in production components and production per plant. Thus, incidence of soil soaking and light restriction in an isolated or combined way negatively affect gas exchange, photosynthetic activity, accumulation of dry mass and grain production of soybean plants.